Evidence based therapeutic outcome of multimodal therapy on sexual decisions of students in River State remedial study centres (2016)
Previous efforts at remediating sexual decision of adolescents in Nigeria have been based on unimodal therapies. Therefore, this study investigated the effectiveness of Multimodal Therapy (MMT) on sexual decisions of adolescents studying in Remedial Centres in Rivers state, Nigeria. Pre-test post control group quasi experimental design with 2x 2 factorial matrix was adopted to execute the study. One hundred and twenty-eight students consisting 71 males (55.4%) and 57 females (44.5%) with age range of 16-21 years (=13.2; SD=3.2) participated in the study. Simple random sampling technique was utilized to draw samples from Remedial Study Centers in River state. Adolescent Decision-Making Questionnaire (r=0.77) was the outcome measure. The experimental group was exposed to nine sessions of MMT (18 hrs) while the control group served as a comparison group. Analysis of Covariance and Multiple x classification analysis were used to test the three hypotheses. There was significant main effect of treatment (F (2,123) =10.871; P<0.05). Male participants had superior treatment gains when compared with the female. These results suggest that Multimodal therapy can be useful in enhancing sexual decision, however programmers should be gender sensitive when designing treatment package.